2018
DOI: 10.1097/aud.0000000000000667
|View full text |Cite
|
Sign up to set email alerts
|

Speech-in-Noise and Quality-of-Life Measures in School-Aged Children With Normal Hearing and With Unilateral Hearing Loss

Abstract: Objectives: 1) Measure sentence recognition in co-located and spatially separated target and masker configurations in school-aged children with unilateral hearing loss (UHL) and with normal hearing (NH). 2) Compare self-reported hearing-related quality of life (QoL) scores in school-aged children with UHL and NH. Design: Listeners were school-aged children (6-12 yrs) with permanent UHL (n = 41) or NH (n = 35) and adults with NH (n = 23). Sentence reception thresholds (SRTs) were measured using HINT-C sentences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
70
4
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(98 citation statements)
references
References 79 publications
(98 reference statements)
8
70
4
2
Order By: Relevance
“…However, the same experimental hardware and software were used at all three testing sites. For a detailed description of the testing facilities and experimental equipment, the reader is referred to Griffin et al (2019). Both acoustical and behavioral measurements reported in that study verified the effective equivalence of the different test booths.…”
Section: Experimental Apparatusmentioning
confidence: 57%
See 3 more Smart Citations
“…However, the same experimental hardware and software were used at all three testing sites. For a detailed description of the testing facilities and experimental equipment, the reader is referred to Griffin et al (2019). Both acoustical and behavioral measurements reported in that study verified the effective equivalence of the different test booths.…”
Section: Experimental Apparatusmentioning
confidence: 57%
“…All children (n = 76, aged 6-12 years) who were subjects in the sentence recognition study reported in Griffin et al (2019) participated in the current comprehension task later in the same 2-hr experimental test session. Forty-one of these children had UHL and 35 had NH.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was full of literature that addressed the intersection of quality of life and noise pollution worldwide. A number of measurement tools were adopted to reflect the relationship between noise and HRQOL, such as WHOQOL-BREF [32], Nijmegen Cochlear Implant Questionnaire [33], SF-36 [34], and Hearing Environments and Reflection on Quality of Life questionnaire [35]. A cross-sectional questionnaire-based study shows that individuals with high noise sensitivity (NS) tend to have degraded HRQOL compared to individuals with low NS [36].…”
Section: Introductionmentioning
confidence: 99%